DICAUVACOOP: A Software Tool to Calculate and Visualize Differentiated Payment According to Grape Quality - Javier Ruiz-Serrano; José C. Berenguer-García; José A. Mateo-Cortés; Enrique Arias-Antúnez (Applied Sciences)
Different physicochemical factors have an influence on wine quality, for instance, quantity of grapes, PH, temperature, and humidity over the growing season. However, despite the weather conditions of the season, the product, grapes, is deposited in the wineries. At that time, a set of analyses are conducted to determine some chemical parameters of the grapes. This work is focused on the chemical parameters obtained at wineries to establish a method to pay farmers according to quality parameters. These parameters have been determined by the technicians at wineries, that is, the experts on wine, as well as market expectations. The idea behind this work is to introduce policies that promote quality instead of quantity, bringing about a change in the mentality of the farmers. These policies pay attention to water consumption or reduction in fertilizers that, of course, affect the chemical parameters of wine but also the sustainability of the sector and the region, in this case, Castilla-La Mancha in Spain. The application developed in this work, called DICAUVACOOP, not only promotes good practices but also introduces penalties. On the other hand, the calculations of each campaign are stored in databases that allow users to conduct comparisons among different campaigns showing the data in a Geographic Information System (GIS) as a decision-making support tool. Another effect of this process is to improve the visibility and brand positioning of Castilla-La Mancha wines on the world stage.